Population structure, genetic variation and morphological diversity in indigenous sheep of Ethiopia - Gizaw, Solomon; Arendonk, Johan A.M. van; Komen, Hans; Windig, J.J.; Hanotte, Olivier H. (Wiley, 2007)
We investigated genetic and morphological diversity and population structure of 14 traditional sheep populations originating from four ecological zones in Ethiopia (sub-alpine, wet highland, sub-humid lowland and arid lowland). All animals (n = 672) were genotyped for 17 microsatellite markers and scored for 12 morphological characters. The sheep were initially classified as fat-tailed (11 populations), thin-tailed (one population) and fat-rumped sheep (two populations). These classifications are thought to correspond to three consecutive introduction events of sheep from the Near-East into East Africa. For the 14 populations, allelic richness ranged from 5.87 to 7.51 and expected heterozygosity (HE) from 0.66 to 0.75. Genetic differentiations (FST values) between all pairs of populations, except between sub-alpine populations, were significantly different from zero (P < 0.001). Cluster analysis of morphological characters and a dendrogram constructed from genetic distances were broadly consistent with the classification into fat-tailed, thin-tailed and fat-rumped sheep. Bayesian cluster analysis using microsatellite markers indicated that there has been further genetic differentiation after the initial introduction of sheep into Ethiopia. Investigation of factors associated with genetic variation showed that an isolation-by-distance model, independently of other factors, explained most of the observed genetic variation. We also obtained a strong indication of adaptive divergence in morphological characters, patterns of morphological variation being highly associated with ecology even when the effect of neutral genetic divergence (FST) was parcelled out in partial Mantel tests. Using a combination of FST values, Bayesian clustering analysis and morphological divergence, we propose a classification of Ethiopian sheep into six breed groups and nine breeds.